2002
DOI: 10.1248/cpb.50.896
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Variation of Acteoside and Three Major Flavonoids in Wild and Cultivated Scutellaria baicalensis Roots by Micellar Electrokinetic Chromatography.

Abstract: H-and 13C-NMR spectral data with that of the authentic compound. This is the first time acteoside has been isolated from the Scutellaria genus. It could only be found in SR derived from wild S. baicalensis roots and 4-year-cultivated plants, but not in plant materials cultivated for 3 years. Applying the MEKC method established in this study, rapid and simultaneous determinations of acteoside together with 3 flavonoids in samples were achieved. The method can thus be used for the quality control of SR in a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
1
8
1
Order By: Relevance
“…However, the levels of baicalin reported in this study and by Zgórka and Hajnos (2003) differed by 4-to 5-fold to the levels reported by Xie et al (2002). Such differences may be due to differences in growth conditions although it is difficult to be certain as exact growth conditions were not reported in some previous reports (Xie et al 2002;Zgórka and Hajnos 2003). Nevertheless, the observation that baicalin is predominantly found in the roots compared to leaves and shoots (in agreement with previous reports) lends credence to our observations not only of S. baicalensis, but also of the other species reported in this study.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…However, the levels of baicalin reported in this study and by Zgórka and Hajnos (2003) differed by 4-to 5-fold to the levels reported by Xie et al (2002). Such differences may be due to differences in growth conditions although it is difficult to be certain as exact growth conditions were not reported in some previous reports (Xie et al 2002;Zgórka and Hajnos 2003). Nevertheless, the observation that baicalin is predominantly found in the roots compared to leaves and shoots (in agreement with previous reports) lends credence to our observations not only of S. baicalensis, but also of the other species reported in this study.…”
Section: Resultscontrasting
confidence: 92%
“…The levels of baicalin observed in S. baicalensis in this study (25.41 ± 0.10 lg mg -1 dry weight of plant material) are similar to levels (19.33 ± 0.72 lg mg -1 dry weight of plant material) reported by Zgórka and Hajnos (2003). However, the levels of baicalin reported in this study and by Zgórka and Hajnos (2003) differed by 4-to 5-fold to the levels reported by Xie et al (2002). Such differences may be due to differences in growth conditions although it is difficult to be certain as exact growth conditions were not reported in some previous reports (Xie et al 2002;Zgórka and Hajnos 2003).…”
Section: Resultssupporting
confidence: 78%
“…Flavonoids can be analyzed by gas chromatography (GC) (Gaydou et al, 1991;Greenaway and Whatley, 1990), high-performance liquid chromatography (HPLC) (Chang et al, 2006;Svedstrom et al, 2002Svedstrom et al, , 2006Wang et al, 2004) and capillary zone electrophoresis (CZE) (Marchart and Kopp, 2003;Urbonaviciute et al, 2006;Wang and Huang, 2004) or micellar electrokinetic capillary chromatography (MEKC) (Wang et al, 2003;Xie et al, 2002). The quality control of hawthorn fruit and leaf are also defined in China Pharmacopoeia (Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Its roots have been used for anti-inflammation, anticancer, antiviral, and antibacterial infections of the respiratory and the gastrointestinal tract, cleaning away heat, moistening aridity, purging fire, detoxifying toxicosis, reducing the total cholesterol level and decreasing the blood pressure. Baicalin, baicalein, wogonin, and oroxylin A are its main active components [84][85][86].…”
Section: Drug Candidatesmentioning
confidence: 99%